The Influence of Field Teaching Practice on Pre-service Teachers’ Professional Identity: A Mixed Methods Study - Zhao, Hongyu; Zhang, Xiaohui (Frontiers in Psychology, 2017)
The current study used mixed methods to research pre-service teachers’ professional identity. Ninety-eight pre-service teachers were investigated and twelve teachers were interviewed in China. The results were as follows: (1) The results of quantitative data showed that compared with before the field teaching practice, pre-service teachers’ professional identity increased after the field teaching practice—specifically, intrinsic value identity increased, and extrinsic value identity did not significantly change; (2) The results of qualitative data validated and elaborated the results of quantitative data in more detail with regard to changes in professional identity. Specifically, compared with before the field teaching practice, intrinsic value identity including work content, work pattern, etc., increased and extrinsic value identity including work environment, income, and social status, etc., did not significantly change after experiencing teaching practice; (3) The results of qualitative data also showed that mentor support at field school promoted the development of pre-service teachers’ professional identity. Moreover, the development of pre-service teachers’ professional identity during field teaching practice further promoted their professional commitment; that is, it promoted their emotional evaluation and belief in the teaching profession. The study discussed these results and proposed solutions and suggestions for future studies.